The Effect of Product Innovation on Purchase Decision Through Purchase Intention as an Intervening Variable at Cafe Kopi Kenangan in Samarinda - Virja Riandi; Istimaroh (Research in Management of Technology and Business, 2024)
Cafe Kopi Kenangan is required to maintain a marketing strategy to exploit market potential to the maximum and spur innovative product creations. This study aims to determine the effect of Product Innovation on Purchase Decisions through Purchase Intention as an intervening variable at Cafe Kopi Kenangan in Samarinda. The population in this study are consumers who have purchased products at Café Kopi Kenangan and have bought at Cafe Kopi Kenangan. This research uses descriptive quantitative type. The sample used in this study was 213 respondents who were taken by probability sampling method using simple random sampling. The data collection technique was carried out using a questionnaire in the form of a Google Form link. The data processing method of this research is using SmartPLS software version 4.0.2. The results in this study indicate that product innovation has a positive and significant effect on purchase decision, product innovation has a positive and significant effect on purchase intention, purchase intention has a positive and significant effect on purchase decision, product innovation has a positive and significant effect on purchase decision through purchase intention as an intervening variable.